Effect of bilateral needling with acupuncture point at SP-6 (Sanyinjiao) on random blood glucose levels in type 2 diabetes mellitus: A Pilot study - kamalakannan, Priyadharshini; Narayanasamy, Mangaiarkarasi; Anandhan, Akila; Narayanasamy, Manavalan (Indian Journal of Integrative Medicine, 2022)
Introduction: Diabetes mellitus (DM) is a metabolic disease, involves improper elevated blood glucose levels. Acupuncture is one of the traditional systems of medicine used in  management of diabetes and its complications worldwide. Objective: This pilot study presents the effect of acupuncture at spleen-6 (SP-6) on Random Blood Glucose levels (RBG) in patients with diabetes mellitus. Methods: Ten Type 2 Diabetes mellitus patients [T2DM] had undergone acupuncture at SP-6 (Sanyinjiao) bilaterally for duration of 30 minutes without any interruption. Assessments were recorded before and after the intervention. Results: The results showed that acupuncture at SP-6 for 30 min duration reduces RBG level significantly in patients with T2DM when compared with baseline assessment. Conclusion: Thus acupuncture at SP-6 could be used to reduce blood sugar level in T2 DM.